Regressing forward: army adaptability and animal power during World War II - Martin, Jason C. (Kansas State University, 2012)
America forged a successful way of war that relied on adaptation, and this trait was not simply an adjunct to industrial might as a reason why the Allies won World War II. An American penchant for organization and corporate management allowed for mass production of war material, which clearly contributed to Axis defeat. However, to claim that the Axis Powers were merely overwhelmed by an avalanche of weapons and supply is reductionist. This dissertation contends that adaptability was as much an American way of war as mass production and overwhelming firepower. The particular nature of American adaptability and its contribution to Allied victory are exhibited in the Army’s use of animal power during a conflict synonymous with mechanized warfare and advanced technology. The application of pre-modern technology in a modern, machine-driven war was not archaic. On the contrary, the nature of American adaptability allowed the Army to move forward by retreating down a culturally constructed hierarchy of modernity and employing the traditional mode of animal transportation. The Army’s technological regression from motors to mules in North Africa, the Mediterranean, and China-Burma-India during World War II is the focus of this work. Americans possessed material abundance in campaigns across Western Europe and the Central Pacific in 1944 and 1945, as German and Japanese prisoners attested. Mountains of artillery shells, fuel, and food, however, did not exist in the backwater “sideshows.” American military success on the periphery was not due to material abundance, nor to a greater sense of determination. America won the backwater campaigns because the nature of American adaptability was cultivated over the centuries and converted from a way of life to an American way of war.
Keywords: Adaptability; World War II; Mules; Army; Animal power; American way of war; History (0578)